Apoptosis In Sepsis - Humardewayanti, Rizka (Acta Interna The Journal of Internal Medicine, 2012)
INTRODUCTIONÂ Â Â Â Â Â Â Â Â Â Â The word sepsis is derived from the Greek term for rotten or âto make putridâ. Sepsis, defined as the systemic host response to microorganisms in previously sterile tissues, is a syndrome related to severe infections and is characterized by end-organ dysfunction away from the primary site of infection. To meet the definition of sepsis, patients need to satisfy at least two of the Systemic Inflammatory Response Syndrome (SIRS) criteria in association with having a suspected or confirmed infection. The severity and mortality increase when this condition is complicated by predefined organ dysfunction (severe sepsis) and cardiovascular collapse (septic shock). The normal host response to infection is complex, aiming to both identify and control pathogen invasion and start immediate tissue repair. Both the cellular and humoral immune systems are activated, giving rise to anti-inflammatory and proinflammatory responses. Exacerbating these mechanisms can cause a chain of events that leads to sepsis, promoting massive liberation of mediators and the progression of multiple organ dysfunction1.Sepsis remains a critical problem with significant morbidity and mortality even in the modern era of critical care management. Despite intense efforts, sepsis remains a serious clinical problem and still associated with a high mortality rate. Septic shock and sequential multiple organ failure/dysfunction syndrome (MOF/MODS) correlate with poor outcome, and septic shock is the most common cause of death in intensive care units. A recent review by Angus et al estimated the 1995 incidence of sepsis in the United States to be 751,000 cases, resulting in 215,000 deaths. The average cost per case of sepsis was 22,100 with total costs of 16.7 billion nationally. A more recent analysis of hospital records indicates that the total number of patients who are dying is actually increasing. This study also confirmed the work of Angus et al that the incidence of sepsis is increasing and projected to continue to grow as the population ages. These studies concluded that âsevere sepsis is a common, expensive, and frequently fatal condition, with as many deaths annually as those from acute myocardial infarction2,3.The immunological cascade resulting in the sepsis response can be initiated by tissue injury, ischemia reperfusion injury, gram-positive organisms, and fungi as well as gram-negative organisms and their constituent endotoxin. The sepsis response may begin with an infectious nidus, which may either invade the bloodstream, leading to dissemination and positive blood cultures, or proliferate locally and release various microbial products into the bloodstream3.Multiple derangements exist in sepsis involving several different organs and systems, although controversies exist over their individual contribution to the disease process. Septic patients have substantial, life-threatening alterations in their coagulation system. Previously, it was believed that sepsis merely represented an exaggerated, hyperinflammatory response with patients dying from inflammation-induced organ injury. More recent data indicate that substantial heterogeneity exists in septic patientsâ inflammatory response, with some appearing immuno-stimulated, whereas others appear suppressed. Cellular changes continue the theme of heterogeneity. Some cells work too well such as neutrophils that remain activated for an extended time. Other cellular changes become accelerated in a detrimental fashion including lymphocyte apoptosis2.The role that apoptosis plays in sepsis syndromes and in the development of CARS and MODS has not been adequately explored, but there is rapidly developing evidence to suggest that increased apoptotic processes may play a determining role in the outcome to sepsis syndromes. In particular, increased apoptosis, particularly in lymphoid tissues and potentially in some parenchymal tissues from solid organs, may contribute to the sepsis-associated MODS3